THAI WORKFORCES’ HAPPINESS: AN ANALYSIS OF FAMILY MANAGEMENT VALUE ON RESOURCES (FINANCE AND KNOWLEDGE), HEALTH, AND EMOTIONAL SUPPORT - Homtrakul, Korakod; Kuntanapa, Napaporn; Piriyakul, Rapepun (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2019)
The ability to work with quality depends on the supporting factors from the family and the organization for achieving work-life balance. Therefore, the organization must manage the workforce based on understanding and responding to the family of the employees as well. For this reason, it is leading to this study with the objectives of studying factors that support the family in three aspects which are in term of resources, health and emotions that affect the happiness of Thai workforces which have work and family balance as intermediate factors. We applied multistage sampling design with sample size 300 from employees who work in retail industry in Bangkok province. The study indicated that emotional sharing factors are the strength of management of Thai families. The other two factors are resources and health sharing are less significant than emotional sharing. Organizations should set policies to encourage employees are able to increase their incomes and have well financial management such as household accounting, promoting health knowledge in every dimension which leads to good resources of the organization.